A study on the influence of reinforcement particle size in laser cladding of TiC/Inconel 625 metal matrix composite. (June 2023) - Bhatnagar, Shrey; Mullick, Suvradip
Highlights: Effect of reinforcement particle (TiC) size on pre-placed laser cladding of MMC. Study of clad geometry and clad-substrate bonding under different size of TiC. Effect of TiC particle size on microstructural evolution and micro-hardness. Correlation of TiC decomposition behavior with molten pool lifetime. Effect of line energy on TiC decomposition behavior and micro-hardness. Abstract: The size of reinforcement particles in laser cladding of metal matrix composite (MMC) plays significant role in defining microstructure and clad properties. The current work investigates the effect of TiC particle size on clad dilution and bonding between clad and substrate, along with microstructural evolution and change in micro-hardness of the deposited layer for single track pre-placed laser cladding of 30 %TiC/Inconel 625 MMC on SS 304 substrate using Yb-Fiber laser. Three different size range of TiC particles were chosen for the experimentations, coarse (particle size: >75 μm), intermediate (size: 25–75 μm) and fine (size: <25 μm). The decomposition behavior of TiC particles and its distribution in clad was observed under different reinforcement particle size and line energy, and the microstructural changes were correlated with molten pool lifetime obtained from the temperature history of the clad layer, captured using IR-Pyrometer. The size of reinforcement particles and their distribution is found responsible for the porosity in pre-placed layer, which finally changes the absorption behavior of laser radiation in powder layer. This further controls the clad dilution, molten pool lifetime and decomposition behavior of TiC particles. The MMC with smaller TiC particles resulted in longer molten pool lifetime and partial decomposition of TiC, resulting in formation of dendrites and leading to higher hardness. However, MMC with very fine TiC resulted in low dilution and improper bonding between clad and substrate. Whereas, MMC with large TiC particles resulted in large dilution and no decomposition of TiC.